EFEKTIVITAS PEMUNGUTAN PAJAK BUMI DAN BANGUNAN DI DESA KAMANGA DUA KECAMATAN TOMPASO KABUPATEN MINAHASA - Mamesah, Frisinthia; PANGKEY, MASJE; KIYAI, BURHANUDDIN (Sam Ratulangi University, 2018)
This research aims to determine the effectiveness of land and building taxcollection in the village of Kamanga Dua, Tompaso Subdistrict. By applying thedescriptive-qualitative method, this research uses the types of primary and secondarydata, then the data is obtained using interview techniques and field observations. Afterand collected then analyzed using percentage analysis techniques to see the effectivenessof UN collection then interview data were also analyzed using interactive techniques.The results showed that: (1) Land and Building Tax Collection in Kamanga DuaVillage, Tompaso Subdistrict, Minahasa District was categorized in principle